A Mechanistic Exploratory Study on the Therapeutic Efficacy of Astragaloside IV Against Diabetic Retinopathy Revealed by Network Pharmacology - Zhao, Zhi-Hao; Xu, Min; Fu, Cong; Huang, Ying; Wang, Ting-Hua; Zuo, Zhong-Fu; Liu, Xue-Zheng (Frontiers in Pharmacology, 2022)
Purpose: Diabetic retinopathy (DR) is a serious complication of diabetes mellitus, which nearly happens to all the diabetic sufferers. This study aims to identify the preliminary molecular regulation involved in the therapeutic efficacy of astragaloside IV (AS- IV) for DR. Methods: Diabetic rat models were established and treated with AS-IV. Optical coherence tomography (OCT) and Hematoxylin-eosin (HE) staining was employed to demonstrated the histopathological changes. The main targets of AS-IV were identified by searching from public databases of traditional Chinese medicine (GeneCards, PharmMapper and Swiss Target Prediction). Besides, disease targets of DR were also obtained by integrated data from GEO datasets and predicted from public databases. Protein-protein interaction (PPI) network was constructed by Cytoscape with overlapping genes and 10 core targets were selected, on which Gene Ontology (GO) along with Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were conducted. The interaction between AS-IV and these crucial genes were analyzed using molecular docking. RT-qPCR and western blot were used to verify the expression variation of core targets. Results: OCT imaging and HE staining demonstrated that AS-IV administration significantly increased retinal thickness in diabetic rats, obviously alleviating DR induced histopathological changes as well as elevated blood glucose levels. 107 common targets of AS-IV and DR were determined after intersection. PPI network analysis filtered 10 hub genes potentially targeted by AS-IV, including VEGFA, CASP3, HIF1α, STAT3, CTNNB1, SRC, AKT1, EGFR, IL1β and IL6. Enrichment analysis indicated that these genes were mainly enriched in biological processes like T cell activation, epithelial cell proliferation and protein kinase B signaling, and involved in oxidative stress, apoptosis and inflammation-related pathways. The molecular docking prediction suggested that AS-IV exhibited stable binding to these core targets. In addition, mRNA levels of core targets in diabetic rats were differentially expressed before and after AS-IV treatment. Western blot further revealed that AS-IV treatment elevated DR-depressed protein levels of PI3K and AKT. Conclusions: Our study elucidated the effect of AS-IV in attenuating retinopathy induced by diabetes in rats and preliminarily unveiled the therapeutic efficacy of AS-IV in the treatment of DR might be attributed to activation of PI3K-AKT signaling pathway.